2021
DOI: 10.1111/ajag.12960
|View full text |Cite
|
Sign up to set email alerts
|

Emergency ambulance demand by older adults from rural and regional Victoria, Australia

Abstract: Objective To describe the demographic profile and clinical case mix of older adults following calls for an emergency ambulance in rural Victoria, Australia. Methods Retrospective cohort study using ambulance electronic patient care records from rural‐dwelling older adults (≥65 years old) who requested emergency ambulance attendance during 2017. Results A total of 84 785 older adults requested emergency ambulance attendance, representing a rate of 278 per 1000 population aged ≥65 years. More than 10% of calls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…We found non-transport in 12.8% of cases in this study; however, when other reasons for non-transport, except patients refusing transport, were excluded, this occurred in only 8.4% of the responses. Younger adults had non-transports approximately twice as often compared with the elderly in previous studies, which we could not confirm in Vienna; our data showed non-transports in elderly patients appearing in 14.0%, which is comparable to 12.3% in Australia and 12.0% in Taiwan and Canada [ 18 , 21 , 22 ]. Thus, many patients are transported to the hospital, meaning that there may potentially be a risk of inappropriate care.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found non-transport in 12.8% of cases in this study; however, when other reasons for non-transport, except patients refusing transport, were excluded, this occurred in only 8.4% of the responses. Younger adults had non-transports approximately twice as often compared with the elderly in previous studies, which we could not confirm in Vienna; our data showed non-transports in elderly patients appearing in 14.0%, which is comparable to 12.3% in Australia and 12.0% in Taiwan and Canada [ 18 , 21 , 22 ]. Thus, many patients are transported to the hospital, meaning that there may potentially be a risk of inappropriate care.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first study to research the epidemiology of the metropolitan EMS utilization of elderly patients in Austria. Response rates were in the upper range when compared to other developed countries [ 2 , 18 , 19 , 20 , 21 , 22 ]. However, the response rates of the younger counterparts should also be considered, due to different EMS systems, depending on different countries, urban or rural locations and high- or low-resource settings.…”
Section: Discussionmentioning
confidence: 86%
“…Low acuity clinical presentations dominate paramedic daily workloads ( Rosser, 2020 ), where older people who have fallen account for 6–8% ( Simpson et al, 2017 ; McManamny et al, 2022 ), and people with mental health problems can account for up to 10% ( Shaban, 2005 ). In contrast, studies have observed that paramedics attend an average of less than two cases of OHCA per year in some areas ( Dyson et al, 2015 ), and whilst studies have struggled to demonstrate association between paramedic experience and survival in treatment of cardiac arrests ( Gold and Eisenberg, 2009 ), survival rates are highest amongst those who received bystander CPR and public access defibrillation ( Hawkes et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Thus, these patients have a greater potential for deterioration during an ambulance journey of 200 km or more, with the generalist nurse as the lead clinician in the absence of trained paramedics. 27 Patient transfer guidelines are key to safe and effective transportation of patients. 17 In this study poor preparation, failure to recognise potential complications during transport, and the use of inexperienced or inappropriate escorts were also highlighted by the RFDS as issue.…”
Section: Discussionmentioning
confidence: 99%